Filmowa Łódź Jadwigi Andrzejewskiej - Roman Włodek (Images)
Before WWII, Jadwiga Andrzejewska 1915–1977) was among the most popular actresses in Polish cinema. During WWII she acted in the Dramatic Theatre of the Polish Second Corps. Returning to her hometown Łódź in 1947 Andrzejewska was initially perceived by the Polish authorities as politically uncertain. Her notable theatrical roles included the heroine in A Woman of Wonder and the heroine in Mother Courage and Her Children. Although she lived in Łódź – a capital of Polish cinema – her film career languished after the war. She had bit parts in about thirty feature films (among them television films). Her biggest and most notable post-war role was in a political propaganda film produced for television, And if Will be Autumn…